Internações hospitalares no Sistema Único de Saúde de Belo Horizonte: 1992-1996 - Leda Lucia Couto de Vasconcelos (1997)
This study was done in order to examine the hospitalizations taken place in Belo Horizonte from 1992 to 1996 by utilizing infomation from the data bank on the form used in the Brazilian health care system to authorize hospital admittance (AIH). The AIH data bank is the largest source of information in Brazil on production by hospitals. In addition, we aimed at verifying whether the implementation of a Belo Horizontes control and evaluation system interfered in the pattem of hospitalizations. The following variables were verified: hospital mortality rate, average lenght of stay, sex, age group and principal diagnosis, average AH-I value, hospital beds and procedures. Some results were as follows: decrease in the number of hospitalizations and in average lenght of stay, increase of mortality rate. Also it was shown that there was a large difference between private and public hospitals. The variables studied enable us to identify some changes in the pattem of hospitalizations, which ocurred not only because of the implementation of Belo Horizontes control and evaluation service, but also mainly because ofthe clear guidance of some specialities.